Test of the LHAASO electron detector prototype using cosmic rays - 徐统业 都艳艳 王旭 邵弱宾 张登峰 祝成光 (Chinese physics C, 2014)
The LHAASO project is to be built in south-west China, using an array of 5137 electron detectors for the measurement of incident electrons arriving at the detector plane. For quality control of the large number of electron detectors, a cosmic ray hodoscope with two-dimensional spatial sensitivity and good time resolution has been developed. The first prototype of the electron detector has been tested with the hodoscope and the performance of the detector is found to be consistent with the design.